Colposcopic Evaluation of Cervical Erosion in Symptomatic Women - Patil , Pooja; Sharma , Priyanka (Advanced Concepts in Medicine and Medical Research Vol. 5, 2023)
This chapter evaluate about Colposcopy and Colposcopic guided biopsies in the symptomatic patients with cervical erosion and correlated these findings with cytology and histopathology. Cancer Cervix is the 2nd most common cancer in women in Low and middle income countries due to poor screening. Many screening methods have been recommended for cervical cancers amongst which pap smear, HPV DNA, Visual Inspection after Acetic acid (VIA), Visual Inspection after Lugol’s Iodine (VILI) and colposcopy are commonly used and recommended. This study is a prospective observational study which was carried out at J. K. Hospital, a tertiary care hospital, from January 2014 to December 2016, with prior permission from Institute ethical committee. All patients coming to Gynec OPD with complaints of white discharge per vagina, itching in private parts, irregular bleeding, inter-menstrual bleeding and post-coital bleeding were subjected to detailed history and gynecological examination. Majority of women came with the complaint of white discharge per vagina (55%). Out of 120 patients, 85 women (70.9%) had inflammatory pap smear and 35 women (29.1%) had abnormal pap smear. All patients underwent colposcopic examination and out of 120 patients, 67(55.8%) showed normal colposcopic findings and 50 women (41.6%) had abnormal colposcopic finding and biopsy was taken. 3 women had unsatisfactory colposcopy. Histopathology confirmed 24 (48%) women with CIN I and 12 (24%) CIN II and 6 (12%) CIN III and 2(4%) women with carcinoma cervix. The colposcopy findings and histopathology correlated in 88%.